Pungutan Pemerintahan Desa Terhadap Masyarakat Sebagai Penyelenggaraan Pemerintahan Desa - Anastasia Pricillia Wibowo (Jurnal HUKUM BISNIS, 2023)
Illegal levies are acts committed by a person or civil servant or state official by requesting payment of an amount of money that is inappropriate or not based on the regulations relating to the payment. It is often equated with extortion. In fact, extortion is the designation of all forms of unofficial levies, which have no legal basis, so the act of levies is referred to as illegal levies (extortion). Illegal levies in most of the cases that occur have an element of abuse of authority. Is there an element of error and criminal responsibility for illegal levies? Abuse of the authority of an official in his position to commit illegal levies part of the core offense. The element against the law is very much needed to determine someone has committed a crime. Is the unlawful element in illegal levies in line with the principle of legality or not. The author realizes the limitations of the author's ability to complete this paper. However, the author hopes that what the author provides in writing this law can be useful for the author personally and all readers.Keywords: illegal levies (extortion) and public services